Understanding gender and language use: A path towards effective interpersonal communication - Irwandi, Irwandi; Fajri, Muhamad; Albert, Albert (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
Research exploring language disparities between men and women from a solely biological standpoint remains limited. Nevertheless, numerous studies have highlighted significant differences in language use, especially within social, political, and cultural contexts. These variations are intricately tied to the social structure, reflecting power dynamics within male-female relationships. Adopting an interpretive approach, the examination of gender disparities in language seeks to uncover social realities shaped by diverse gender roles and relationships. Moreover, this inquiry delves into the importance of grasping these linguistic variances to facilitate effective interpersonal communication. Understanding such nuances is pivotal for navigating and bridging potential communication barriers, fostering more meaningful and inclusive interactions across various social landscapes. By acknowledging and comprehending these distinctions, individuals can enhance communication efficacy and foster mutual understanding between genders.